English Language Education Situation in India - Meganathan, Ramanujam (JOURNAL OF INDIAN EDUCATION, 2015)
This paper attempts to present the current state of English language education in schools in India through a reflection of policies and practices. Different types of schools in the different school systems, typologies of teaching situations are presented with illustrations and the diverse nature of curriculum, syllabus and materials development and the quality issues related to it. It goes on to suggest measures to improve the quality of English language education in schools.